Hemodynamic Patterns Identified by Impedance Cardiography Predict Mortality in the General Population: The PREVENCION Study. Issue 18 (18th September 2018) - Medina‐Lezama, Josefina; Narvaez‐Guerra, Offdan; Herrera‐Enriquez, Karela; Morey‐Vargas, Oscar L.; Bolaños‐Salazar, Juan Francisco; Abugattas, Juan P.; Zea‐Diaz, Humberto; Chirinos‐Revilla, Jose L.; Fernandez‐Sivincha, Jenny G.; Delgado‐Lazo, Victor; Chirinos, Diana A.; Townsend, Raymond R.; et al.
Abstract : Background: Blood pressure is determined by the interactions between the heart and arterial properties, and subjects with identical blood pressure may have substantially different hemodynamic determinants. Whether arterial hemodynamic indices quantified by impedance cardiography (ICG), a simple operator‐independent office procedure, independently predict all‐cause mortality in adults from the general population, and specifically among those who do not meet criteria for American College of Cardiology/American Heart Association stage 2 hypertension, is currently unknown. Methods and Results: We studied 1639 adults aged 18 to 80 years from the general population. We used ICG to measure hemodynamic parameters and metrics of cardiac function. We assessed the relationship between hemodynamic parameters measured at baseline and all‐cause mortality over a mean follow‐up of 10.9 years. Several ICG parameters predicted death. The strongest predictors were total arterial compliance index (standardized hazard ratio=0.38; 95% confidence interval=0.31–0.46; P <0.0001) and indices of cardiac contractility: velocity index (standardized hazard ratio=0.45; 95% confidence interval=0.37–0.55; P <0.0001) and acceleration index (standardized hazard ratio=0.44; 95% confidence interval=0.35–0.55; P <0.0001). These remained independently predictive of death after adjustment for multiple confounders, as well as systolic and diastolic blood pressure. Among subjects without stage 2 hypertension (n=1563), indices of cardiac contractility were independently predictive of death and identified a subpopulation (25% of non‐stage‐2 hypertensives) that demonstrated a high 10‐year mortality risk, equivalent to that of stage 2 hypertensives. Conclusions: Hemodynamic patterns identified by ICG independently predict mortality in the general population. The predictive value of ICG applies even in the absence of American College of Cardiology/American Heart Association stage 2 hypertension and identifies higher‐risk individuals who are in earlier stages of the hypertension continuum.